Events, States and Times. An essay on narrative discourse in English - Altshuler, Daniel (De Gruyter, 2016)
This monograph investigates the temporal interpretation of narrative discourse in two parts. The theme of the first part is narrative progression. It begins with a case study of the adverb 'now' and its interaction with the meaning of tense. The case study motivates an ontological distinction between events, states and times and proposes that 'now' seeks a prominent state that holds throughout the time described by the tense. Building on prior research, prominence is shown to be influenced by principles of discourse coherence and two coherence principles, NARRATION and RESULT, are given a formally explicit characterization. The key innovation is a new method for testing the definitional adequacy of NARRATION and RESULT, namely by an abductive argument. This contribution opens a new way of thinking about how eventive and stative descriptions contribute to the perceived narrative progression in a discourse.